The (q; k)-Analogues of Some Inequalities Involving the Psi Function - Nantomah, Kwara (Global Journal of Mathematical Analysis, 2014)
In this paper, the (q; k)-analogues of some inequalities involving the Psi function are presented. These resultsgeneralize some earlier results presented by W. T. Sulaiman. The approach is based on some mononicity propertiesof some functions involving the (q;k)-Psi function.Keywords: Psi function, (q; k)-analogue, Inequality.MSC: 33B15, 26A48.